2021
DOI: 10.5781/jwj.2021.39.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between HAZ Microstructure and Low Temperature Impact Toughness of Bainitic Steel Plates

Abstract: In this study, the correlation between HAZ microstructure and low temperature impact toughness of bainitic steel plates was investigated. The Steel with high carbon content and finish cooling temperature has a higher volume fraction and large packet size of granular bainite compared to the steel with low carbon content and finish cooling temperature. The room temperature tensile properties of the two steels are similar, mostly because the microstructure is composed of acicular ferrite having fine grains. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, more discussion should be carried out for detailed understanding the influence of Ti, Nb precipitates, since previous studies have confirmed the side effect of grain refinement in high heat input welding owing to the increasing fraction of grain boundary ferrite, which can have a negative influence on impact toughness 24) . It was also reported that bainitic ferrite may contribute to the toughness drop in the CGHAZ 25,26) . Fig.…”
Section: Resultsmentioning
confidence: 90%
“…However, more discussion should be carried out for detailed understanding the influence of Ti, Nb precipitates, since previous studies have confirmed the side effect of grain refinement in high heat input welding owing to the increasing fraction of grain boundary ferrite, which can have a negative influence on impact toughness 24) . It was also reported that bainitic ferrite may contribute to the toughness drop in the CGHAZ 25,26) . Fig.…”
Section: Resultsmentioning
confidence: 90%
“…The HAZ comprises coarse-grained HAZ (CGHAZ), ne-grained HAZ (FGHAZ), and intercritical HAZ (ICHAZ) away from the fusion line of the WM [28][29][30][31][32][33]. The CGHAZ and FGHAZ were composed primarily of martensite (M) and bainite (B) owing to rapid cooling from the peak temperature of the full austenite region.…”
Section: Microstructural Behaviours Of Transverse Welds Under Various...mentioning
confidence: 99%